The EU Directive on the Disclosure of Non-Financial and Diversity Information - A New Challenge for Accounting - Kamela-Sowińska, Aldona (Studia Oeconomica Posnaniensia, 2014)
This paper has two principal aims. The first one is to indicate the direction of changes in accounting from classical accounting towards economic reporting. The second aim of this article is to raise questions, problems and issues related to accounting which will have to be addressed by the academic community to assist practitioners in implementing the tasks and objectives of modern accounting included in the directive. The article is not an analysis of the direct impact of the changes introduced by the directive on valuation and the disclosure of value in accounting. It only points to the increasing role of corporate social responsibility (CSR) in accounting and the scale of this phenomenon. The paper presents the author’s own analysis of the possible effects of the introduction of new accounting rules in EU countries, with only fairly limited references to the literature because no national or international publications on the current directive are available to date. The conclusions of the article are prescriptive in nature and attempt to identify areas for further detailed scientific research. The article applies the practical aspects of economic knowledge which makes it possible to use this in the selection and quantification of economic objectives, the design of systems and organizational goals, as well as the selection of resources to effectively achieve the set objectives. From the point of view of macroeconomics, the research method focuses on economic reporting as a tool for building a global economy. From the point of view of accounting, the article uses the theory of principlebased accounting as well as the normative theory of accounting. The article lists nine key issues which at this stage need to be addressed by researchers and subsequently put to practical use in the implementation of the directive.